Specificity of Dynamic Changes in Offline Retail Marketing - Dimova, Nadezda (Research Papers, 2023)
As a result of many changes in the economy and society, the marketing that is implemented in the retail trade is changing. The inseparable relationship between it and retail is of particular importance for the overall existence and development of any company, regardless of its size.Although neglected offline marketing is important, even if the percentage ratio compared to online marketing is falling, this type of marketing has its place and importance in physical stores. It is a competitive advantage for managers to keep track of the specific dynamic changes in offline retail marketing, which is the subject of this report.